KARAKTERISTIK PENDERITA PERJALANAN PENYAKIT SERTA PENYAKIT PENYERTA PENDERITA DIABETES MELLITUS tipe 2 DENGAN NEUROPATI DIABETIK di RSUP SANGLAH DENPASAR - Thomas Eko P * , Kumara Tini.** (NEURONA, 2009)
BACKGROUND DIABETIC NEUROPATHY IS ONE OF THE MOST COMMON COMPLICATION IN DIABETES NERVE DAMAGE ACCOUNT FOR HIGH MORBIDITY AND MORTALITY IN DIABETIC PATIENTS IDENTIFICATION AND EARLY DETECTION DIABETIC NEUROPATHY RISK FACTOR LEAD TO BETTER PREVENTION AND MANAGEMENT OF DIABETIC NEUROPATHY